Bio-Electric-Electronics and Tissue Engineering Applications of MXenes Wearable Materials: A Review - Gürbüz, Berfin; Çiftçi, Fatih (Elsevier, 2024)
In the realm of bioelectronics, MXenes exhibit remarkable conductivity and compatibility with biological systems, making them pivotal in the development of neural interfaces and biosensors. Their efficient signal transduction capabilities contribute to precise monitoring of physiological processes, enhancing the field’s diagnostic and therapeutic potential. MXenes also play a crucial role in tissue engineering, where their unique combination of mechanical strength and biocompatibility contributes to scaffold materials that promote cell adhesion, proliferation, and differentiation. This aspect holds promise for advancing regenerative medicine by facilitating the creation of biomimetic tissue constructs. Furthermore, MXenes find applications in electrical devices, demonstrating superior performance in energy storage solutions, electrocatalysis, and electronic components. Their use in supercapacitors and batteries enhances energy storage efficiency, addressing critical challenges in renewable energy systems. In wearable technology, MXenes contribute to flexible and conductive materials, enabling the integration of advanced components into wearable devices. This includes applications in smart textiles, biosensors, and electronic skin, exemplifying the versatility of MXenes in shaping the future of wearable materials. In conclusion, this review underscores the multifaceted nature of MXenes and their transformative impact on bioelectronics, tissue engineering, electrical applications, and wearable materials, positioning them as key players in the forefront of interdisciplinary research and technological innovation.
Keywords: MXenes; Bioelectronics; Tissue engineering; Electrical; Wearable material